Biological and Chemical Diversity of Biogenic Volatile Organic Emissions into the Atmosphere. (17th June 2013) - Guenther, Alex
Abstract : Biogenic volatile organic compounds (BVOC) emitted by terrestrial ecosystems into the atmosphere play an important role in determining atmospheric constituents including the oxidants and aerosols that control air quality and climate. Accurate quantitative estimates of BVOC emissions are needed to understand the processes controlling the earth system and to develop effective air quality and climate management strategies. The large uncertainties associated with BVOC emission estimates must be reduced, but this is challenging due to the large number of compounds and biological sources. The information on the immense biological and chemical diversity of BVOC is reviewed with a focus on observations that have been incorporated into the MEGAN2.1 BVOC emission model. Strategies for improving current BVOC emission modeling approaches by better representations of this diversity are presented. The current gaps in the available data for parameterizing emission models and the priorities for future measurements are discussed.